2019
DOI: 10.1038/s41598-019-53702-4
|View full text |Cite|
|
Sign up to set email alerts
|

New insight into the mechanisms of ectopic fat deposition improvement after bariatric surgery

Abstract: Non-alcoholic fatty-liver disease (NAFLD) is frequent in obese patients and represents a major risk factor for the development of diabetes and its complications. Bariatric surgery reverses the hepatic features of NAFLD. However, its mechanism of action remains elusive. We performed a comprehensive analysis of the mechanism leading to the improvement of NAFLD and insulin resistance in both obese rodents and humans following sleeve-gastrectomy (SG). SG improved insulin sensitivity and reduced hepatic and monocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 38 publications
2
23
0
Order By: Relevance
“…Hepatic AMPK and CPT1α transcripts were studied by RT PCR and were proven to be significantly decreased as compared to controls [ 201 ]. In accordance with these findings it was recently shown that NASH patients showed significantly reduced hepatic AMPK expression and Thr172 αAMPK phosphorylation [ 202 ]. Therefore, one hypothesis arising from available molecular evidence in humans suggests increasingly upregulated cellular DNL in early stages of NAFLD, with hepatic AMPK and fat oxidation capacity becoming initially increased in a compensatory manner.…”
Section: Dysregulation Of Hepatic Ampk In Humanssupporting
confidence: 78%
“…Hepatic AMPK and CPT1α transcripts were studied by RT PCR and were proven to be significantly decreased as compared to controls [ 201 ]. In accordance with these findings it was recently shown that NASH patients showed significantly reduced hepatic AMPK expression and Thr172 αAMPK phosphorylation [ 202 ]. Therefore, one hypothesis arising from available molecular evidence in humans suggests increasingly upregulated cellular DNL in early stages of NAFLD, with hepatic AMPK and fat oxidation capacity becoming initially increased in a compensatory manner.…”
Section: Dysregulation Of Hepatic Ampk In Humanssupporting
confidence: 78%
“…Our results also provided relevant information about the effects of metabolic surgery on adipose tissue dysfunction. Quantitative and qualitative changes in visceral and ectopic fat composition has been documented in magnetic resonance studies [ 9 , 24 , 25 , 26 ] and even molecular signatures of metabolic surgery have been recently described in the adipose tissue [ 27 ]. There would be then the opportunity for new adiposity-related biomarkers to emerge and address some of the current shortcomings in metabolic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The improvement in insulin sensitivity after bariatric surgery is related to an improvement in plasma inflammatory biomarkers [112], as well as to a reduction in liver [114,115] and muscle fat accumulation [112,116], and to changes in subcutaneous adipose tissue histology with a consequent reduction of the adipocytes area and of the peri-adipocytes inflammation [112]. However, despite the large weight loss observed after surgery, insulin sensitivity does not completely normalize and sparse macrophages (mainly in T2D patients) are still present in SAT [112,117].…”
Section: Insulin Sensitivitymentioning
confidence: 99%